Using a fire propagation model to assess the efficiency of prescribed burning in reducing the fire hazard - Cassagne, Nathalie; Pimont, Francois; Dupuy, Jean-Luc; Linn, Rodman R.; Mårell, Anders; Oliveri, Chloé; Rigolot, Eric (Ecological Modelling, 2011)
We examined how ﬁre hazard was affected by prescribed burning and fuel recovery over the ﬁrst six years following treatment. Eight common Mediterranean fuel complexes managed by means of prescribed burning in limestone Provence (South-Eastern France) were studied, illustrating forest and woodland, garrigue and grassland situations. The coupled atmosphere-wildﬁre behaviour model FIRETEC was used to simulate ﬁre behaviour (ROS, intensity) in these complex vegetations. The temporal threshold related to the effectiveness of prescribed burning in reducing the ﬁre hazard was assessed from derivated fuel dynamics after treatment. The study showed that prescribed burning treatment was effective for the ﬁrst two years in most of the Mediterranean plant communities analysed. Thereafter, all forests and shrublands were highly combustible with a ﬁre line intensity of more than 5000 kW/m except for pine stands with or without oak (medium intensity of 2000 kW m−1 3 years after treatment). Low ﬁre line intensity (900 kW m−1 ) was obtained for grassland which was entirely treatment-independent since the resprouter hemicryptophyte, Brachypodium retusum, is highly resilient to ﬁre. Fire behaviour was greatly affected by fuel load accumulation of Quercus ilex in woodland, and by standing necromass of Rosmarinus ofﬁcinalis in treated garrigue. Pure pine stands with shrub strata similar to garrigue showed a lower ﬁre intensity due to wind speed decrease at ground level under tree canopy, underlining the advantage of maintaining a proportion of canopy cover in strategic fuel-break zones
Keywords: Fire behaviour; FIRETEC; Fuel dynamics; Mediterranean fuel complexes; Prescribed burning

Diversification of Pinus halepensis forests by sowing Quercus ilex and Quercus pubescens acorns: testing the effects of different vegetation and soil treatments - Prévosto, Bernard; Monnier, Yogan; Ripert, Christian; Fernandez, Catherine (European Journal of Forest Research, 2010)
The goal of this study was to develop management strategies favouring establishment and survival of holm oak (Quercus ilex L.) and downy oak (Quercus pubescens Willd.)—two species co-occurring in Southern France—in mature Allepo pine forests (Pinus halepensis Mill subsp. halepensis). An experimental design was assessed in a partially cut mature stand of Aleppo pine in which ﬁve soil and vegetation treatments—chopping, chopping followed by scariﬁcation in one or two directions, prescribed burning, control—and two slash treatments (presence/absence) were applied. A total of 1,600 sowing points, each composed of 3 Q. ilex or Q. pubescens acorns, were installed in the different treatments in November of two consecutive years at 6 and 18 months, after the end of treatments. Survival was monitored 3 and 2 years after sowing, soil surface at the sowing points was characterized at different dates, and predawn leaf water potentials were measured during the dry season. High mortality occurred after the ﬁrst summer, but survival after 1 year was 2.3–5.2 higher in Q. ilex than in Q. pubescens, conﬁrming that Q. ilex was better adapted to the drier parts of the Mediterranean area. Survival was signiﬁcantly inﬂuenced by the treatments, but there was a variable response between the two sowing years under most of the treatments. Only intense ﬁre proved the most beneﬁcial treatment for seedling survival in both years. The micro-local soil cover conditions induced by the treatments played a major role in explaining oak survival. In particular, grass cover (mainly Brachypodium retusum) proved to be largely unfavourable to seedling survival and growth, and this detrimental effect was also conﬁrmed by lower predawn leaf water potential values with increasing grass cover. Acorn introduction designed to diversify mature Aleppo pine forest after soil and vegetation treatments therefore has to be considered for treatments that most efﬁciently impair the pre-existing competing grass cover such as prescribed high-intensity ﬁre treatment.
Keywords: mediterranean oaks; Prescribed burning; seedling growth; seedling survival; Stand regeneration; Vegetation control